Settlement of Domestic Violence Crimes Through Restorative Justice - Johan Pieter Elia Rumangun (LUTUR Law Journal, 2025)
Domestic violence (DV) is a serious problem that impacts victims not only physically but also psychologically and socially. In Indonesia, domestic violence is a pressing social issue that requires effective resolution. According to data from the National Commission on Violence Against Women, the rate of domestic violence in Indonesia continues to rise, encompassing physical, psychological, sexual, and economic violence. The persistence of this problem indicates that the system for handling domestic violence cases still faces numerous challenges. This research is empirical and juridical. The research method is descriptive-analytical. The legal sources used are primary legal materials, secondary legal materials, and secondary legal materials. Data collection techniques used were interviews and questionnaires. The results indicate that resolving domestic violence cases through restorative justice involves several key factors: Investigators consider the severity of the violence, the perpetrator's willingness to take responsibility, and the goodwill of both parties to resolve the issue peacefully. Investigators at the Aru Islands Police Department focus on restoring relationships between perpetrators and victims, with the goal of reducing long-term social and psychological impacts and avoiding a backlog of cases in court. Restorative Justice has demonstrated significant effectiveness in resolving Domestic Violence (DV) cases when implemented appropriately. This approach provides space for perpetrators to take responsibility for their actions, for victims to receive psychological recovery, and to repair damaged relationships. However, its effectiveness depends heavily on several factors, such as the perpetrator's readiness to accept responsibility, the victim's willingness to participate, and support from law enforcement officials in terms of counseling and guidance.